Exfoliative cytology of the oral mucosa: Comparison of two collection methods - Queiroz, Juliana Brusadin; Lima, Celina Faig [UNESP]; Burim, Rafael Augusto; Brandao, Adriana Aigotti Haberbeck; Cabral, Luiz Antonio Guimaraes; Almeida, Janete Dias (My University, 2010)
This study compared the sampling efficacy cia cytobrush and metal spatula for exfoliative cytology of the oral mucosa. Thirty students with no detectable oral alterations upon clinical examination were submitted to exfoliative cytology of the lateral border of the tongue, using a metal spatula on the left side and a cytobrush on the right side. The smears were stained using the Papanicoiaou technique and evaluated for cellularity, cell type, cell distribution, homogeneity, and cellular distortion, as well as the presence ol mucus, inflammatory infiltrate, and hemorrhage. A statistical test (Z-test) with a 95% confdence interval (Cl) showed a significant difference between the metal spatula and cytobrush in terms of cellularity (p = 0.02) and homogeneity (p = 0.01). No difference between the two methods was observed regarding cell type (p = 0.4, Z-test) or cell distribution for the 95% confidence interval (p = 0.2, Fisher's test). Cell distortion and the presence of mucus were observed in five cases that used the metal spatula and in two cases that used the cytobrush. No hemorrhage or inflammatory infItrate was detected in any of the slides. Based on the results of this study, the cytobrush produced qualitatively better smears in terms of cellularity and homogeneity compared to the metal spatula.
Keywords: coloring agent; diagnostic agent; cell shape; comparative study; cytodiagnosis; cytology; epithelium cell; equipment design; human; inflammation; instrumentation; methodology; mouth mucosa; mucus; oral bleeding; pathology; tongue; Cell Shape; Coloring Agents; Cytodiagnosis; Epithelial Cells; Equipment Design; Humans; Inflammation; Mouth Mucosa; Mucus; Oral Hemorrhage; Tongue